Nanotextured alpha Ni(II)-Co(II) hydroxides as supercapacitive active phases - Arencibia, Nicolas (2017)
A family of monophasic nanoplatelets of Ni(ii)-Co(ii) layered hydroxides, were obtained by a one-pot room temperature homogeneous alkalinization driven by the the epoxide route with glycidol. Both cations precipitate in the form of solid solutions, giving the general formula Ni1-xCox(OH)2-yCly·nH2O. Co(ii)-rich samples developed the simonkolleite-like alpha structure in which cations can adopt either octahedral (Oh) or tetrahedral (Td) environments, according to the formula (Ni,Co)Oh1-xCoTd2x(OH)2-2x(Cl)2x·nH2O. Ni(ii)-rich ones resulted in ill-crystallized turbostratic (Ni,Co)1-x(OH)2-x(Cl)x·nH2O. Despite the inherent differences in the crystallochemical nature of theses phases, electrochemical measurements depict a monotonous behavior in terms of their capacitance. An optimum performance was observed for samples with XNi(II) = 0.83 under most of the experimental conditions explored. This sample reaches a maximum specific capacitance of 2091 F g-1, registered at a discharge current density of 0.5 A g-1, while an energy density of 80.7 W h kg-1 was recorded at a power density of 960.4 W kg-1.